INFECTION WITH A NOVEL CORONA VIRUS (2019-nCoV) (The PRESENT RISK AND THE CHALLENGE) - (A Brief Review) - KAMAL ALSAAD (Basrah Journal of Veterinary Research)
In late December, 2019, patients presenting with suspected of viral pneumonitis due toan non-identified microbial agent were reported in Wuhan, China. A novel coronaviruswas subsequently identified as the causative pathogen, provisionally named 2019 novelcoronavirus (2019-nCoV). As of Jan 26, 2020, more than 2000 cases or more of 2019-nCoV infection have been confirmed, most of which involved people living in or visitingWuhan, and human-to-human transmission has been confirmed.